Gambaran School Health di Sekolah Menengah Atas Negeri Jabodetabek - Luciana Pricilia; Sumarani Sukmarani (Universitas Muhammadiyah Jember, 2023)
School health is a condition where school organizations have technical, managerial and institutional level which is conformable and able to fulfill basic needs as well as other needs for the sake of improving the school and overcoming external strength distracting school’s objectives or missions. The purpose of this research is to see the overview of school health in Public Senior High Schools of Greater Jakarta. The research method is a descriptive method using quantitative approach. The sampling method used is purposive sampling method. Participants in this research are 62 teachers who are working in Public Senior High Schools in Greater Jakarta. The participants consist of 2 Vice Principals and 60 teachers whose status is temporary and full-time employees, with S1 and S2 educational background. The data are obtained by using the scale of Organizational Health Inventory-Secondary. The research result shows that institutional integrity dimension belongs to medium category, principal influence dimension belongs to high category, Consideration dimension is in high category. The principal influence in medium category and resources support dimension in medium category. The morale dimension is in high category and the academic emphasis is in high category.